The judicial control over the constitutionality of laws in the State of Palestine - Ahmed M A Hamad; Emad Mohammad Al Amaren; Omar Farouk Al Mashhour; Kukuh Tejomurti; Haslinda binti Mohd. Anuar; Rohizan binti Halim (Faculty of Law, University of Muhammadiyah Malang, 2020)
This article aimed to explore judicial control over the constitutionality of laws in the State of Palestine. The article problem was represented in the authority involved with judicial control over the constitutionality of laws in Palestine, and what is the legal effect of ruling on the unconstitutionality of specific legislation. The judicial control is meant the constitutional judiciary undertakes to examine the constitutionality of laws and regulations issued by the Legislative Council or the President of State, to determine whether they are in conformity with the constitution or are in violation of it. This article uses normative legal research using the legislation approach and doctrinal approach. The importance of this article is that it has been discussed the legal framework governing judicial control of the constitutionality of laws in Palestine, and sheds light on the concept of judicial control, its mechanisms, nature, and effects to ensure the protection and consolidation of constitutional texts. In order to achieve the objective of this study, the socio-legal research using the qualitative approach was engaged to describe and analyze the opinions of jurists, legal texts, and rulings of constitutional courts in Palestine. Among the most important results that the author reached is that the state of law cannot be established without adopting the principle of judicial control over the constitutionality of laws to protect the legal texts that exist within the constitution, which is the supreme law within the legislative hierarchy.